Traço unário: o suporte da distintividade - Tatiana Pedrozo de Sousa Pinto (2014)
In "The Instance of the Letter in the Unconscious, or Reason Since Freud" (1957/1998) Lacan formalizes his structural approach inscribed in his return to Freud. Underlining transposition, or Entstellung, as the basics dream's mechanism while a unconscious formation, Lacan introduces his concept of signifier. This way, Lacan departs of the structuralist view, extracted from Saussure, locating the significant as the main element for reading the key concepts of Freudian psychoanalysis, from where the idea of unconscious structured as a language arises. Moreover, structuralism was chosen by Lacan as an instrument for his return to Freud. We know that saussurian's sign is composed of a relationship of signifier to signified. However, taking the signifier, despites of what's proposed by Saussure, Lacan underlines the importance of the bar that separates these elements that compose the sign. Thus, that wich leads to the signification effect, the bar's surpassing, is hampered and extremely evanescent. With this model, the chain asks for the tireless signifier's saying to create sense. Therefore, a point where the chain anchor itself is needed in order to think a subject that is not consumed by anguish produced by speaking without generating sense or social bond. This anchoring point is commonly treated in the theorization as "button ties" [points de capiton], or 'quilting point'. Since the signifier chain runs continuously, our aim in this dissertation was to understand how it stops and which concepts are related to this mechanism. In order to do so we showed how Lacan defines this mechanism in the seminar on the psychoses (J. Lacan, 1985 [1955-1956]) and how it has been reworked from the seminar on Identification (J. Lacan, 2003 [1961-1962]) with the notion of unary trait. For this last concept, the unary trait, we consider that it became the center of this dissertation, since it was our main goal sift its assumptions and implications.